SHARIA PRINCIPLES IN WEALTH MANAGEMENT: THEORY AND PRACTICE - Windari; Sugianto; Marliyah (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
Sharia-based wealth management is increasingly important in the context of global finance that demands a fair and ethical approach. This article aims to explore the application of sharia principles in wealth management, with a focus on the challenges and opportunities faced in practice. This study uses a qualitative method with data collection through interviews and observations in Islamic financial institutions to understand how these principles are applied in day-to-day operations. The data used include interviews with financial institution managers, customers, and sharia experts, as well as document analysis related to wealth management policies and practices. The results of the study indicate that although Islamic financial institutions have great potential to improve community welfare through ethical wealth management, they still face various challenges in implementing sharia principles consistently. Interesting findings from this study indicate that the lack of understanding of sharia financial products among the community is a major obstacle. In addition, inconsistent regulations also reduce the effectiveness of the application of sharia principles in practice. The implications of this study indicate the need to improve sharia financial literacy among the community and develop clearer regulations to support the growth of this sector.